2021
DOI: 10.1021/acsanm.1c00380
|View full text |Cite
|
Sign up to set email alerts
|

BiOCl-Coated UiO-66-NH2 Metal–Organic Framework Nanoparticles for Visible-Light Photocatalytic Cr(VI) Reduction

Abstract: Pollutants in wastewater, such as Cr(VI) is a continuous threat to our ecological system and human well-being because of its high noxiousness and latent carcinogenicity. Photocatalytic Cr(VI) reduction is the most suitable and eco-friendly way to convert the toxic Cr(VI) to environmentally friendly Cr(III). Porous metal−organic frameworks (MOFs) based nanocomposites are emerging green photocatalysts for Cr(VI) reduction due to their unique characteristics such as high photoconductivity, large surface area, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…The decrease in the catalytic performance at pH = 2 was noticed because the ZnS-ZCH micro-belt could be unstable at strongly acidic condition. 28 Additionally, the effect of reaction temperature on the reduction efficiency was studied and the data are presented in Fig. 6D.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in the catalytic performance at pH = 2 was noticed because the ZnS-ZCH micro-belt could be unstable at strongly acidic condition. 28 Additionally, the effect of reaction temperature on the reduction efficiency was studied and the data are presented in Fig. 6D.…”
Section: Resultsmentioning
confidence: 99%
“…Hussain et al successfully synthesized BiOCl@UiO-66-NH 2 composite and degraded Cr(VI) under visible light. [8] The results showed that the reaction rate constant K is 35.8 and 19.6 times higher than isolated UiO-66-NH 2 and BiOCl, respectively. The MIL-53@BiOCl composite photocatalyst was prepared by Sheng Chao et al [15] The degradation rates of Rhodamine B by MIL-53@BiOCl-6 in 30 min was 59.2 %, while BiOCl and MIL-53 were about 39.2 % and 24.1 %, respectively.…”
Section: Introductionmentioning
confidence: 92%
“…Because of its cheap, non-toxic and stable characteristics, it is widely used in the field of photocatalytic degradation. [8][9][10] However, the lack of optical response in visible light limits its development. The current research shows that the performance of photocatalyst can be improved by constructing heterojunction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations